Dynamic changes of activated partial thromboplastin time and correlation with mortality in patients with severe fever with thrombocytopenia syndrome: A retrospective cohort study. - Huan Wang; Sisi Fang; Hua Wang; Xin Zheng (PLoS Neglected Tropical Diseases)
Background Hemorrhagic manifestations are highly prevalent in severe fever with thrombocytopenia syndrome (SFTS) patients and are significantly associated with fatal outcomes. In this study, we investigated the dynamic changes of activated partial thromboplastin time (APTT) and their association with mortality in SFTS patients. Methods We conducted a retrospective study analyzing clinical data from SFTS patients admitted to our hospital between April 2017 and June 2024. The dynamic changes of APTT and their association with clinical outcomes were analyzed. Results A total of 788 SFTS patients were enrolled in this study, among whom 96 (12.18%) died during hospitalization. Multivariate logistic regression identified prolonged APTT as an independent predictor of mortality, along with older age, neurological symptoms, higher viral load, and elevated creatinine levels. Prolonged APTT was observed in 568(72.08%) patients upon admission and was associated with the development of neurological symptoms, bleeding, intensive care unit (ICU) transfer, and mortality. APTT≥2.0 times the upper limit of normal (ULN) was associated with significantly higher mortality (55%) and an increased likelihood of ICU transfer (10%). Restricted cubic splines (RCS) analysis revealed that when the APTT level exceeded specific thresholds (49.86s upon admission and 53.61s at the peak during hospitalization), the predicted mortality of patients with SFTS increased with rising APTT levels. Kinetic analysis showed that APTT levels exhibited a declining trend during hospitalization and returned to the normal range by the 6th day in the survival group, while it gradually increased, reaching its peak on the 3rd day and then gradually decreased in the non-survival group. Conclusion Prolonged APTT was prevalent among SFTS patients and was significantly associated with higher mortality. Monitoring APTT upon admission and its dynamic changes during hospitalization is recommended to enhance the management of SFTS patients.